Shisha Consumption Patterns: Knowledge, Attitudes, and Practices Among Kolkata University Students - Syed, Sadia Asif; Asad, Safia (Journal of Research in Vocational Education, 2025)
Introduction: Shisha commonly known as hookah, water pipe, or narghile, is a method of smoking flavoured and non- flavoured tobacco, where the smoke passes through water before inhalation. It consists of a bowl, stem, water base, hose, and mouthpiece. This traditional form of tobacco consumption is particularly common in Middle Eastern and South Asian countries and often perceived as a safer alternative to traditional cigarettes. Method: This a cross-sectional study design, conducted using a simple random-sampling method at a premier institute, Kolkata. Using a modified version of the WHO GYTS questionnaire to collect samples. A total of 307 complete responses were considered for data analysis, P value <0.05 was considered statistically significant. Result: Out of 307 participants, males (41.1%) and female (59.9%), age group of 18-20 years (46.6%). Reported current smokers (24.4%), daily smokers (19.9%). Product preferred to smoked- Cigarettes (31.3%), shisha (7.8%). Students’ awareness of shisha (44%), and had tried shisha (27.7%), and 26.4% have used it for more than three years. Age between 18-20 years was a significant factor shisha consumption (p <0.001). Students believed shisha is less harmful than cigarettes (p =0.007) and considered it safe to smoke for a year or two (p =0.006). Most of female students felt sales of shisha to minor (<18-year-old) should not be banned (p =0.009). Conclusion: Shisha consumption is prevalent among students due to lack of stringent regulation, peer influence and desire of new experience. Many students hold a misconception relating to its health risk, often view it as a safer alternative to cigarettes. Target health campaign is essential to address false beliefs and enforcing a stronger policies and tobacco free campus initiatives can help to reduce access and protect student well-being.